Evolution of global crustal uplift and subsidence and basins - Yuzhu KANG (Shiyou shiyan dizhi, 2020)
The earth's crust is under various stresses including compressive stress, tensile stress and torsional stress, resulting in uplift, subsidence, depression and strike-slip. The tectonic movement caused uplifts and depressions in the crust, leading to changes in the land and sea. During the geological evolution history, the crust uplifted into orogenic belts or uplift areas, while depressions changed to various types of basins. Global basins can be divided into five major types, namely rift-craton, intracratonic depression, foreland, fault and depression ones. There are eight major deformation styles in the global structure, namely, east-west, north-south, north-east, north-north-east, north-west, epsilon-shaped, S- or reversed-S shaped, and twisted ones. Oil and gas in the Paleozoic cratonic basins of China are mainly distributed in paleo-uplifts, paleo-slopes, regional unconformities, and fault zones. In Mesozoic and Cenozoic faulted basins, oil and gas are mainly distributed in steep slopes, gentle slopes, and central structural belts. In Mesozoic and Cenozoic foreland basins, oil and gas are distributed in fault fold belts, slope belts and overthrust belts. Various twisted structures, such as broom-shaped, echelon, knob-shaped, reversed S-shaped, and λ-shaped ones, control oil and gas distribution.